(untitled) (Research, Society and Development, 2021)
Background: Dengue is an endemic viral disease transmitted by mosquitoes of the species Aedes aegypti and Aedes albopictus that causes a fall in the host’s immune system due to overload in fighting the virus and leaves the body more susceptible to opportunistic infections. The odontogenic infection can have its condition aggravated in patients infected with dengue, making the treatment more complex. Objective and case report: The objective is to make a case report of a 15-year-old patient, without systemic comorbidities who was diagnosed with dengue (DENV) and element 16 odontogenic infection, affecting the maxillary sinus, maxillary and right subpalpebral oral space. The treatment was carried out, noting a delay in the response of the clinical improvement of the odontogenic infection, showing the need for prevention of the two common clinical conditions. Conclusion: Suggesting that dengue can worsen the condition of dental infection due to changes in the patient’s immunological conditions, making treatment difficult.